Three new species of the Encarsia inaron (Hymenoptera: Aphelinidae) species group from China with a key to Chinese species - Geng, Hui; Li, Cheng-De (Zootaxa, 2017)
Five species of the inaron-group of Encarsia Förster (Hymenoptera: Aphelinidae) from China are reviewed, including the description of three new species, E. dongbeiana Li & Geng, sp. nov., E. imiza Li & Geng, sp. nov., and E. polymacula Li & Geng, sp. nov. New distributional data for E. inaron (Walker) and E. azimi Hayat are provided and a key to Chinese species of E. inaron-group is given based on females.